In Reply. (25th July 2013) - Valachis, Antonis; Polyzos, Nikolaos P.
Abstract : Our meta‐analysis provides evidence that zoledronic acid in the adjuvant breast cancer setting may increase survival. Additional data from basic research and clinical trials in the future will help us interpret its role with more confidence.